Improvement of surface roughness of aluminum products by the micro-grooves on tool surface in cold extrusion - Kamitani, S.; Nakanisi, K.; Syahrullail, S. (Keikinzoku Gakkai/Japan Institute of Light Metals, 2008)
The effects of the micro-groove arrays formed on the tool surface on the material flow, surface condition of a billet and surface quality of a product were investigated by carrying out the plane strain extrusion experiments. Paraffinic mineral oil and RBD palm olein were applied in the above experiments. The distributions of flow velocity and effective strain in a billet were analyzed by using the visio-plasticity method. The experimental and analytical results show that the extrusion load increases with the inflow of billet to the grooves. The results also show that the surface condition of the extruded product is smoother when the location of the micro-groove array is at the inner section in the deformation boundary and a paraffinic mineral oil was used. The surface quality of a product in an extrusion process could be improved, under a slight rise of the extrusion load by using a tool with micro-groove arrays were formed on the tool surface at an appropriate section.